Suitability of earthen materials for rammed earth in arid region - Hasan Eanas; Al-Sharrad Muayad (Magazine of Civil Engineering)
This study investigated the suitability of two engineered earthen materials manufactured by mixing different proportions of sand, silt, and clay for rammed earth constructions under dry conditions. The first mix contained 30 % fine material, whereas the second mix contained 50 % fine material. Test specimens were prepared by static compaction to 4.5, 25, 50, and 100 MPa, equilibrated at relative humidity values of RH = 35 % and RH = 55 % and tested in the lab to characterize plasticity, mechanical, hydric, and thermal behavior. The materials showed a drying shrinkage of no more than 4 %, depending on the initial water content and the unit weight of the material. The results indicated a remarkable increase in materials elastic stiffness and strength of 50 % to 120 % and 10 % to 70 %, respectively, with increasing dry unit weight or compaction energy. The increase in soil suction led to a profound improvement in stiffness and strength, owing to an increase in capillary bonding. In addition, the increase in finer content from 30 % to 50 % significantly enhanced the mechanical behavior. If a minimum compressive strength of 2 MPa is considered, then compacting the earthen material to 50 MPa or greater would provide sufficient strength under the operational humidity RH=55 %. For the mix with 50 % finer content, a compressive strength of almost 5.75 MPa was achieved when the material was compacted to 100 MPa and equalized to RH = 55 %. As relative humidity increased, materials strength decreased where the amount of reduction was found to be inversely proportional to the compaction level and the maximum dry unit weight. The dynamic adsorption behavior was, largely, independent of the amount of compaction energy or finer content. The dynamic adsorption test indicated that the tested materials exchange a considerable amount of moisture with the atmosphere. Compared to traditional brick and concrete blocks, the materials showed good insulation characteristics. It was observed that the increase in finer content yielded slightly higher thermal conductivity values. Overall, the engineered material examined in this work can be potentially used for rammed earth under dry conditions.